Analysis of Factors Affecting Interest in Choosing Departments in Madrasah Aliyah in Pekanbaru City - Agustin, Sri; Indrawati, Henny; Gimin, Gimin (FKIP-Universitas Riau, 2021)
This study aims to analyze the factors which affect the interests of majors in Madrasah Aliyah in Pekanbaru City. Total population of 1225 students with samples as many as 302 students obtained pro proportionately random sampling. Data collection using questionnaires and documentation. Then the data were analyzed descriptively and analyzed by Structural Equation Model (SEM). The results showed: (1) Parents' attention has a direct and significant effect on the interest in choosing a major, meaning that the greater the attention of parents, the higher the student's interest in choosing a major. (2) Parent’s attention and ideals not directly affect academic ability, and academic ability does not affect the interest of majors. it means that the size of the parents' attention and the student's aspirations does not affect the student's academic ability and interest in the chosen major. (3) Ambition job directly affects the interest to choose a major, which means that the level of ambition will be in line with how much desire and interest in the majors since according to their interests. This shows that interest in choosing a major can increase along with increasing parental attention and student ambitions.